The elimination of human African trypanosomiasis: Monitoring progress towards the 2021-2030 WHO road map targets. - Jose R Franco; Gerardo Priotto; Massimo Paone; Giuliano Cecchi; Agustin Kadima Ebeja; Pere P Simarro; Dieudonne Sankara; Samia B A Metwally; Daniel Dagne Argaw (PLoS Neglected Tropical Diseases, 2024)
Background Human African trypanosomiasis (HAT) is a neglected tropical disease that usually occurs in rural areas in sub-Saharan Africa. It caused devastating epidemics during the 20th century. Sustained, coordinated efforts by different stakeholders working with national sleeping sickness control programmes (NSSCPs) succeeded in controlling the disease and reducing the number of cases to historically low levels. In 2012, WHO targeted the elimination of the disease as a public health problem by 2020. This goal has been reached and a new ambitious target was stated in the WHO road map for NTDs 2021-2030 and endorsed by the 73rd World Health Assembly: the elimination of gambiense HAT transmission (i.e. reducing the number of reported cases to zero). The interruption of transmission was not considered as an achievable goal for rhodesiense HAT, as it would require vast veterinary interventions rather than actions at the public health level. Methodology/principal findings Data reported to WHO by NSSCPs were harmonized, verified, georeferenced and included in the atlas of HAT. A total of 802 cases were reported in 2021 and 837 in 2022. This is below the target for elimination as a public health problem at the global level (< 2000 HAT cases/year); 94% of the cases were caused by infection with T. b. gambiense. The areas reporting ≥ 1 HAT case/10 000 inhabitants/year in 2018-2022 cover a surface of 73 134 km2, with only 3013 km2 at very high or high risk. This represents a reduction of 90% from the baseline figure for 2000-2004, the target set for the elimination of HAT as a public health problem. For the surveillance of the disease, 4.5 million people were screened for gambiense HAT with serological tests in 2021-2022, 3.6 million through active screening and 0.9 million by passive screening. In 2021 and 2022 the elimination of HAT as a public health problem was validated in Benin, Uganda, Equatorial Guinea and Ghana for gambiense HAT and in Rwanda for rhodesiense HAT. To reach the next goal of elimination of transmission of gambiense HAT, countries have to report zero cases of human infection with T. b. gambiense for a period of at least 5 consecutive years. The criteria and procedures to verify elimination of transmission have been recently published by WHO. Conclusions/significance HAT elimination as a public health problem has been reached at global level, with seven countries already validated as having reached this goal. This achievement was made possible by the work of NSSCPs, supported by different public and private partners, and coordinated by WHO. The new challenging goal now is to reach zero cases by 2030. To reach this goal is crucial to maintain the engagement and support of donors and stakeholders and to keep the involvement and coordination of all partners. Along with the focus on elimination of transmission of gambiense HAT, it is important not to neglect rhodesiense HAT, which is targeted for elimination as a public health problem in the WHO road map for NTDs 2021-2030.